Representation and peasant imagination: Life after the gaze of a catechist (Cajamarca, Peru) - Mujica Bermúdez, Luis (2004)
The representations made by Guamán Poma de Ayala, those presented by Martínez de Compañón, those disseminated by the painters of Sarhua, the paintings by Carmelón Berrocal and many other anonymous artists are dense textual forms in which diagnoses of reality, the denunciations or rejections of certain situations and the insinuations of utopias that would like to build a tinkuy, an encounter; that is to say, they are aesthetic spaces where the traces of perceptions and feelings, as well as the brushstrokes of desires and expectations, are artistically combined thanks to the skill and tenderness of the draftsman or painter, creating a "book open to the eyes of the readers."